"Sanitation and Ventilation as required in a Modern House": a review of by-laws in the 1890s relating to toilets in New Zealand Housing - Isaacs, Nigel (Architectural History Aotearoa, 2023)
Good public sanitation has a long history in New Zealand, with Joseph Banks recording on 21 October 1769: "Every House or small knot of 3 or 4 has a regular necessary house where every one repairs and consequently the neighbourhood is kept clean." Although piped water was in main city centres (e.g. Dunedin, Wellington) by the 1860s, it was not until the 1880s that it became common in houses. By the 1890s "earth" or "water" closets were built onto laundry outhouse or at the farthest corner of the garden. As the population of cities increased, public health issues became more important, requiring the introduction of by-laws. As well as issues of sanitation, the by-laws were concerned with fire and public decency. The paper will review the evolution of council by-laws dealing with privies and toilets in Wellington in the 1890s.